Tourism Management After COVID: Recovery and Resilience - Putu Gita Suari Miranti (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2023)
This study examines the dynamics of tourism management in the aftermath of the COVID-19 pandemic. The unprecedented global health crisis severely impacted the tourism industry, resulting in travel restrictions, economic disruptions, and shifts in traveler behavior. Using a mixed-methods research approach, this study investigates the challenges and opportunities faced by tourism destinations and businesses, with a focus on the impact of COVID-19 on traveler behavior, technological advancements, sustainable practices, collaboration, and policy frameworks. The findings reveal the profound effects of the pandemic on tourism management and highlight the need for adaptive strategies, technological innovations, sustainable practices, stakeholder collaboration, and effective policy frameworks to navigate the path to recovery and resilience. The study contributes to the scholarly understanding of post-pandemic tourism management and provides valuable insights for industry stakeholders, policymakers, and researchers seeking to shape the future of the tourism sector.